Mauritian Hinduism and globalisation : transformation and reinvention - Chazan-Gillig, Suzanne, 1940-; Ramhota, Pavitranand, 1956-; Mishra, Sriniket Kumar (Abingdon, Oxon : Routledge, 2023)
"This book presents an original and comprehensive overview of the transformation of Mauritian Hinduism against the backdrop of globalisation. It discusses themes such as the cult of Baharia Puja; the cult of "Camp De Masque"; changes in popular cults; temples and associative strategies of social integration; emergence of Hanuman; ritual innovations in politics and, religious and political transformation due to globalisation to highlight the link between the reinvention of Hinduism and Mauritian capitalism. First of its kind, this book with its rich ethnographic accounts, will be an essential read for scholars and researchers of religion, Hinduism, social anthropology, sociology, cultural studies, diaspora studies, sociology of religion and African studies"--
The Cult of "Baharia Puja" in "Camp De Masque Pave" at Kalimai of "Petite Cabanne" -- The "Amourou Puja" Cult of "Camp De Masque" -- The Transformation of Popular Cults on "Crown Lands" -- Kalimais Temples and Associative Strategies: The Emergence of Hanuman -- The New Deal: Religious and Political Transformation -- Kalimai Temple Transformations and Changes in Rituals.
Keywords: Hinduism -- Mauritius; Folk religion -- Mauritius; Globalization -- Religious aspects -- Hinduism; RELIGION / Hinduism; RELIGION / General